Assessing the coverage and representativeness of the national incident-based reporting system - McCormack, Philip D. (Crime & delinquency, 2017)
This article examines the coverage of the National Incident-Based Reporting System (NIBRS) as of 2013. We use NIBRS, Uniform Crime Reports (UCR), and Supplementary Homicide Reports to assess the population coverage and index crime coverage of NIBRS. We also examine the correspondence of crime rates between the UCR and agencies that do and do not participate in NIBRS. We found that NIBRS covers 29.3% of the U.S. population and 28% of UCR index crimes. We also found that the crime rates in NIBRS jurisdictions are appreciably lower than jurisdictions that do not participate in NIBRS. As of 2013, therefore, NIBRS data are not representative of the U.S. population, crime counts, or crime rates.